Energy as a Social and Commercial Determinant of Health: A Qualitative Study of Australian Policy - Fran Baum; Michael P. McGreevy; Colin M. MacDougall; Mark Henley (Kerman University of Medical Sciences, 2023)
Background  This paper considers energy as a social and commercial determinant of health. Stable access to clean and sustainable energy is integral for human wellbeing yet public health rarely considers its importance. Methods  Using NVivo qualitative analysis software we analysed all Australian federal, state and territory strategic energy policies covering varying periods between 2016-2030. We defined strategic policy as including the goals, objectives and strategies of the department regarding a specific area of policy responsibility. This criterion excluded documents such as operational guidelines. 36 energy-related policies were analyzed. Results  While the nature of energy supply is crucial to determining the impact of human and environmental health, our analysis showed that health and wellbeing are only rarely considered in policy. We developed a conceptual framework to guide our work linking energy policy with health. Australia's continued reliance on fossil fuels evident in the policies poses health risks, especially as climate change threatens physical and mental health. Yet health considerations were mainly absent from the policies. However, some jurisdictions (South Australia and the Australian Capital Territory [ACT]) had policies encouraging a fast move to renewables. Energy pricing was a key focus in each jurisdiction and had become highly politicalized in the past decade. Little attention was paid to equity considerations in the policies. Conclusion  Energy policy would be more health promoting if public health perspectives were considered during its development. On the basis of our policy analysis and literature review we conclude with recommendations for healthy energy policy.